Understanding affirmative action : politics, discrimination, and the search for justice - Kellough, J. Edward (Georgetown University Press, 2006)
For some time, the United States has been engaged in a national debate over affirmative action policy. A policy that began with the idea of creating a level playing field for minorities has sparked controversy in the workplace, in higher education, and elsewhere. After forty years, the debate still continues and the issues are as complex as ever. While most Americans are familiar with the term, they may not fully understand what affirmative action is and why it has become such a divisive issue. With this concise and up-to-date introduction, J. Edward Kellough brings together historical, philoso.